Different 21st Century Skills Among Z Generation in The Higher Education Based On The Level of Students, and Gender Difference - Suciani Latif; Nur Fadhilah Umar; Yasdin Yasdin (Universitas Negeri Makassar, 2022)
Z Generation is a generation that is unique from the previous generation because it has technological capabilities and lives in an era of advanced technology. This uniqueness requires Z generation to have 21st-century skills to adapt to the demands of the industrial era 4.0. However, not all Z Generation have these skills and adaptability. Therefore, this study aims to describe and distinguish the skills of 21st-century students as seen from the level of lectures and gender differences. This type of research is descriptive quantitative research. The sample in this study amounted to 268 students from 9 faculties, namely Education, Language, Engineering, art, psychology, social science, sports, economics and science. This sample consisted of 130 women and 138 men. The measuring instrument in this study uses an adaptation of the 21st-century skill instrument, which consists of 4 aspects: 1) Information and technology literacy skills, 2) Entrepreneurship and innovation skills, 3) Social responsibility and leadership skills, and 4) career consciousness. Techniques of data analysis using descriptive statistical data analysis and ANOVA using JASP assistance. The results showed that there were differences in students' 21st-century skills based on semester level, and there were differences in students' 21st-century skills based on gender.